Structural Characterization of Peruvian Carrot (Arracacia xanthorrhiza) Starch and the Effect of Annealing on Its Semicrystalline Structure - Rocha, Thais S. [UNESP]; Cunha, Verena A. G. [UNESP]; Jane, Jay-lin; Franco, Celia M. L. [UNESP] (Amer Chemical Soc, 2011)
Structural characteristics of native and annealed Peruvian carrot (Arracacia xanthorrhiza) starches were determined and compared to those of cassava and potato starches. Peruvian carrot starch presented round and irregular shaped granules, low amylose content and B-type X-ray pattern. Amylopectin of this starch contained a large proportion of long (DP > 37) and short (DP 6-12) branched chains. These last ones may contribute to its low gelatinization temperature. After annealing, the gelatinization temperatures of all starches increased, but the Delta H and the crystallinity increased only in Peruvian carrot and potato starches. The annealing process promoted a higher exposure of Peruvian carrot amylose molecules, which were more quickly attacked by enzymes, whereas amylopectin molecules became more resistant to hydrolysis. Peruvian carrot, starch had structural characteristics that differed from those of cassava and potato starches. Annealing affected the semicrystalline structure of this starch, enhancing its crystallinity, mainly due to a better interaction between amylopectin chains.
Keywords: Starch; Arracacia xanthorrhiza; annealing; Structure; Amylose; Amylopectin